The Role of Resources, Capabilities, and Digitalisation in Accelerating Internationalisation Process among Malaysian Small and Medium Enterprises - Lee, Yan Yin (2020)
The main objective of the study is to understand the key internal determinants that could affect Malaysian SMEs’ competitive advantages in international markets. International Entrepreneurship studies suggest resources and capabilities drive SME internationalisation. Nevertheless, there is lack of research evidence that gives insight about what resources and capabilities will lead to SMEs’ competitive advantages in international markets, especially in emerging countries like Malaysia. Apart from resources and capabilities, digitalisation and its interaction with competitive advantages in international markets have not been widely discussed. This study develops a research model for testing of the direct relationships of resources, capabilities, digitalisation on competitive advantages in international markets. The model also tests the indirect relationships of resources and digitalisation on competitive advantages through capabilities. Using MATRADE directory to target Malaysian exporting SME manufacturers, this study employs quota sampling method for distribution of v questionnaire. Based on 143 responses, partial least square structural equation modeling (PLS-SEM) was used for data analysis. The research findings reveal the distinctive role of resources and capabilities for different types of competitive advantages in international markets. Management international resources contribute to price advantage, international capabilities contribute to product and service advantages, while digitalisation has no direct effect to any of these competitive advantages. Nevertheless, these two constructs are important for SME internationalisation owing to their indirect effects on product and service advantages. The research is valuable for Malaysian SMEs that wish to internationalise or strengthen their competitiveness in international markets. The main practical implication is that by having an evidence-based understanding of the resources and capabilities that accelerate internationalisation and SMEs can conduct international business easier with reduction of time, money and risks. In conclusion, SMEs should develop the right sets of resources (management characteristics, international knowledge, network) and capabilities (marketing, innovation, learning capabilities) for gaining of competitive advantages in international markets. They may also enhance both resources and digitalisation in developing their international capabilities.